IMPLEMENTASI ANALYTICAL HIERARCHY PROCESS (AHP) PADA SISTEM PENDUKUNG KEPUTUSAN PURCHASING DALAM PENENTUAN PEMBELIAN PRODUK PRIORITAS STUDI KASUS TOKO DKIDS MEDIA BERBASIS WEB - Arsyifa Putri, Jihan; Yose Eduar Muda; Subhan Munafis (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
A maximum 200 words abstract in English in italics with Times New Roman 10 points. Abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods and a summary of the results. Abstract should end with a comment about the importance of the results or conclusions brief. There are no citations, tables or figures in abstract.